APLIKASI FORMULA PUPUK HAYATI DAN KOMPOS PADA TANAH MARJINAL UNTUK PERTUMBUHAN TANAMAN CABAI MERAH (Capsicum annum L.) - Ratny Witanti Arista; Nur Laili; Eko Handayanto (Jurnal Tanah dan Sumberdaya Lahan, 2018)
Rhizosphere bacteria isolated from the soil were screened and characterized based on their ability as PGPR (Plant Growth Promoting Rhizobacteria) bacteria. The biofertilizer formula made from this bacteria was be applied to the marginal Ultisols collected from the Cibinong Science Center area and tested for its potential on the growth of red chili plants. The treatments tested were Formula 1, Formula 2, POH StartMik, inorganic fertilizer, and control. The results showed the ability of the formulas 1 and 2 to provide nutrients, especially P for the growth of red pepper plant. Formula 2 could increase P nutrient by 90.91 mg kg-1, provide available P by 86.0 mg kg-1 and PMEase enzyme activity was also available at 54.26 mg kg-1.